The High Potential of Computer-Based Reading Assessment - Pauline Auphan; Jean Ecalle; Annie Magnan (The Canadian Network for Innovation in Education (CNIE), 2020)
The aim of this study is to propose advantages provided by computerized tools when assessing reading ability. A new computer-based reading assessment evaluating both word reading and reading comprehension processes was administered to 687 children in primary (N=400) and secondary (N=287) schools. Accuracy (weighted scores) and speed of access (response times) automatically recorded by the software were analyzed based on developmental issues (Anovas), correlation matrices, structural equation modeling and clinical interpretation. Results underlined the validity and reliability of the tool. The Discussion addresses the limitations of the present computer-based assessment and presents perspectives for taking fuller advantage of computerized technologies.